Adding pregabalin to a multimodal analgesic regimen does not reduce pain scores following cosmetic surgery : a randomized trial - Chaparro, Luis Enrique; Clarke, Hance; Valdes, Paola A.; Mira, Mauricio; Duque, Lorena; Mitsakakis, Nicholas (Journal of anesthesia, 2012)
Purpose Multimodal analgesia increases the chance of successful discharge and pain control after surgery, and pregabalin is being promoted as an effective analgesic, based on placebo-controlled studies. We investigated whether adding pregabalin improved pain control and reduced opioid requests when it was added to a multimodal analgesic regimen for cosmetic surgery. Methods One hundred and ten women who underwent same-day cosmetic surgery were randomized to receive oral pregabalin, 75 mg q12 h for five consecutive days starting the night before surgery, or identical placebos. Participants, outcomes assessors, and the statistician were blinded. The primary outcome was postoperative numerical movement-evoked pain scores at 2, 24, 48, 72, and 96 h after surgery. The secondary outcomes included pain scores at rest; incidence of moderate to severe pain; and analgesic and antiemetic requirements; as well as the incidence of nausea, vomiting, and somnolence. Results Based on 99 patients who completed the study, we found no difference between the groups in the primary outcome; 72 h after surgery, movement-evoked median pain scores were <4/10 in both groups. We found no differences in opioid requirements ( p = 0.95) or anti-inflammatory requirements ( p = 0.45), and no difference in opioid-related adverse events. Conclusion Perioperative pregabalin 75 mg twice a day does not increase benefit when it is added to an already multimodal analgesic regimen for patients undergoing cosmetic surgery. Several factors could explain our findings, including the possibility of publication bias in the current literature.